2020
DOI: 10.1088/1361-6528/ab7535
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nano-conjugate on Drosophila for early diagnosis of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is an irreversible neurodegenerative disease. Recent identification of AD biomarkers has led to the diagnosis of AD before the onset of dementia. It has been shown that Drosophila melanogaster is a valuable model for studying human neurodegeneration, including AD. According to its properties, curcumin shows promising potential for the diagnosis of AD. In order to improve its use, new formulations, including nanotechnology-based delivery systems, have been applied. The current study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…One of these probes was shown to enter brain when administered iv, and fluorescence in vivo imaging revealed that it remained for a significantly longer period of time in Tg2576 brain compared with WT mice, suggesting that it had successfully labeled amyloid in Tg2576 mice [99,100]. Zinc induces oligomerisation of amyloid β, and, similar to results in mammals, curcumin fluorescence clearly separated ZnCl 2 -induced Alzheimer flies (Drosophila) from control flies following oral administration of curcumin-conjugated carbon-dot nanoparticles [101]. Interestingly, Aβ42 from AD patient plasma was bound and sequestered by liposomes functionalised with phosphatidic acid or with a modified Apolipoprotein E-derived peptide or with a curcumin derivative, suggesting a possible future use of the liposomes as a "peripheral sink" [102].…”
Section: Diagnostic Tool For Amyloidmentioning
confidence: 67%
“…One of these probes was shown to enter brain when administered iv, and fluorescence in vivo imaging revealed that it remained for a significantly longer period of time in Tg2576 brain compared with WT mice, suggesting that it had successfully labeled amyloid in Tg2576 mice [99,100]. Zinc induces oligomerisation of amyloid β, and, similar to results in mammals, curcumin fluorescence clearly separated ZnCl 2 -induced Alzheimer flies (Drosophila) from control flies following oral administration of curcumin-conjugated carbon-dot nanoparticles [101]. Interestingly, Aβ42 from AD patient plasma was bound and sequestered by liposomes functionalised with phosphatidic acid or with a modified Apolipoprotein E-derived peptide or with a curcumin derivative, suggesting a possible future use of the liposomes as a "peripheral sink" [102].…”
Section: Diagnostic Tool For Amyloidmentioning
confidence: 67%
“…159 In another study, curcumin-loaded CDs were used for diagnosing Alzheimer's disease (AD). 160 Similarly, Chung and coworkers prepared branched polyethyleneimine (bPEI) conjugated CDs using ammonium citrate, to treat AD by acting as an anti-Alzheimer's b-amyloid (Ab) neurotoxin agent. 161 Mehta et al demonstrated that due to the multifunctional groups on CD surfaces, CDs can be employed as multifunctional vehicles for drug loading and release.…”
Section: Drug Deliverymentioning
confidence: 99%
“…159 In another study, curcumin-loaded CDs were used for diagnosing Alzheimer's disease (AD). 160 Similarly, Chung and coworkers prepared branched polyethyleneimine (bPEI) conjugated CDs using ammonium citrate, to treat AD by acting as an anti-Alzheimer's β-amyloid (Aβ) neurotoxin agent. 161…”
Section: Advantages Of Red Carbon Dotsmentioning
confidence: 99%
“…The dysfunctional brains of insects enable us to learn more about human brain diseases. In the AD Drosophila model for example, appearance of degenerated neurons and signs of edema in the hippocampus improve our understanding about what is happening 16 . In PD Bombyx mori model, The p -translucent silkworm is caused by downregulation of the DJ-1 gene, resulting in an increase in the oxidative stress response of the body, which leads to oxidative damage to the nerves and tissues 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%